EFFUSIVE-CONSTRICTIVE PERICARDITIS POST SURGICAL REVISION FOR IATROGENIC HEMOPERICARDIUM - Kolek, Martin (Biomedical papers, 2011)
Aim: A case report of subacute effusive-constrictive pericarditis in a patient with iatrogenic hemopericardium is presented.Methods: A 69-year-old man was referred to our department for percutaneous coronary intervention complicated with hemopericardium with cardiac tamponade. Continuous bleeding after pericardiocentesis required an urgent surgical revision with evacuation of hemopericardium and local treatment of the sources of bleeding. A mild to moderate pericardial effusion persisted in the post-operative period, without any symptoms of cardiac tamponade. A global heart failure developed in the patient eleven months after complicated coronary intervention (surgical revision). A technically successful pericardiocentesis did not improve the clinical state of the patient. Echocardiography and magnetic resonance imaging confirmed the diagnosis of effusive-constrictive pericarditis.Results: Subsequent pericardiectomy resulted in a prompt and complete relief of symptoms and signs of heart failure.Conclusion: Effusive-constrictive pericarditis is an uncommon disorder characterised by symptoms of refractory cardiac failure, thickening of the visceral pericardium and pericardial effusion, with no improvement after pericardiocentesis. In indicated cases, pericadiectomy leads to recovery in a large percentage of patients.
Keywords: Percutaneous coronary intervention/Hemopericardium/Pericarditis/Pericardiocentesis/Pericardiectomy